Specific absorbed fraction of energy and relative dose in some polymers. (2022) - Nagaraja, N.; Manjunatha, H.C.; Seenappa, L.; Sridhar, K.N.; Ramalingam, .H.B.; Sowmya, N.
Abstract: We, in this work investigated the specific absorbed fraction (SAF) of energy, energy absorption buildup factors (ABFs) and relative dose (RD) in the energy range 15 keV–15 MeV for some polymers such as Zylon (C14 H6 O2 N2 ), Technora (C34 H24 O5 N4 ), Mylar (C10 H8 O4 ), Twaron (C14 H10 O2 N2 ), Bakalite (C14 H12 O2 ) and Orlon (C3 H3 N) up to the penetration depth (PD) of 40 mfp using GP fitting method. With the increase in the penetration depth, buildup factors increase. It is observed that the values of shielding parameters like effective atomic number (EAN), buildup factor (BF) and mass attenuation coefficient (MAC) are larger for the polymer Technora (C34 H24 O5 N4 ) than the other studied polymers. SAF of energy is maximum for the polymer Technora (C34 H24 O5 N4. Hence, we can conclude that the polymer Technora (C34 H24 O5 N4 ) is a good absorber of X-rays, neutrons and gamma among the investigated polymers. This work finds its usefulness in the shielding of radiation.